Reducing the Cranial CT Rate for Pediatric Minor Head Trauma at Three Community Hospitals. Issue 2 (March 2019) - Smith, Alla; Gruskin, Karen; Monuteaux, Michael C.; Stack, Anne M.; Sundberg, Melissa; Yim, Ramy; Seneski, Annie; Becker, Theresa
Abstract : Objective: Efforts to reduce the rate of computerized cranial tomography (CT) in pediatric patients with minor head trauma (MHT) have focused on academic medical centers. However, community hospitals deliver the majority of pediatric emergency care. We aimed to reduce cranial CT utilization in patients presenting with MHT at 3 community hospital emergency departments (EDs). Methods: Multidisciplinary stakeholder teams at each site oversaw the quality improvement effort, which included education about an evidence-based guideline for MHT and individual provider feedback on CT rates. Given the variation in hospital structure, we tailored the specifics of the intervention to each site. We used statistical process control methodology to measure CT rates over time. The primary balancing measure was returned to the ED within 72 hours with clinically important traumatic brain injury. Results: We included 3, 215 pediatric ED visits for MHT: 1, 253 in the baseline period and 1, 962 in the intervention period. The CT rate dropped from 18% in the baseline period to 13% in the intervention period, a 28% relative reduction. Pediatric providers saw 72% of the intervention period encounters and drove this reduction. There was no increase in the number of children who returned to their local ED within 72 hours with clinically important traumatic brain injury. Conclusions: We safely reduced the proportion of children with MHT who received a cranial CT through a multicenter community ED quality improvement initiative. We did not see an increase in missed clinically important traumatic brain injury.